Smartcampus Hub: A Python-Based Student Enrollment and Event Ticketing Management System Using Object-Oriented Programming (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The SmartCampus Hub: A Python-Based Student Enrollment and Event Ticketing Management System Using Object-Oriented Programming is a desktop application developed using Python, Tkinter for the graphical user interface, and a database management system (such as SQLite or MySQL) for data storage and retrieval. The system is designed to automate student enrollment processes and campus event ticketing operations, reducing manual paperwork and improving administrative efficiency.The application provides modules for student registration, course enrollment, event creation, ticket issuance, attendee tracking, and report generation. By applying Object-Oriented Programming (OOP) principles, the system achieves better code organization, maintainability, scalability, and reusability. Database integration enables persistent storage of student records, enrollment transactions, event details, and ticket information, while Tkinter provides an interactive and user-friendly interface for administrators and students.The system was developed following standard software development practices, including requirements analysis, design, implementation, testing, and evaluation. Testing results indicate that the application can efficiently manage enrollment and event-related transactions while maintaining data accuracy and consistency. The study demonstrates that combining Python, Tkinter, and a relational database can produce a practical, cost-effective, and scalable campus management solution suitable for educational institutions.